Species Identification and Morphometric Analysis of Bats (Chiroptera) in Saung Cave, Pengembur Village, Central Lombok - Elwis, Khalid; Syaputra, Maiser; Sari, Diah Permata (Jurnal Biologi Tropis, 2025)
Bats play a crucial role in maintaining the balance of ecosystems, particularly in controlling insect populations. This study focuses on identifying the bat species (Chiroptera) in Saung Cave, Pengembur Village, Pujut Subdistrict, Central Lombok Regency, and exploring their morphological characteristics. The research aims to determine the types of bat species found in the cave and their respective morphometric features. Data were collected using the trap method with mist nets. Descriptive data analysis was used to present the data, while quantitative analysis was applied to the morphometric measurements, including body weight, body length, wingspan, ear length, tail length, tragus, and antitragus. The study identified five bat species: Pro-bruk hutan (Rhinolophus affinis), Pro-bruk lonkos (Rhinolophus acuminatus), Kubar Janggut Hitam (Taphozous melanopogon), Lasiwen Biasa (Myotis muricola), and Barong Besar (Hipposideros diadema). The bats found in Saung Cave exhibit varying sizes, with differences between males and females. Notably, males of Pro-bruk hutan (Rhinolophus affinis), Pro-bruk lonkos (Rhinolophus acuminatus), and Lasiwen Biasa (Myotis muricola) tend to be larger than females, while females of Barong Besar (Hipposideros diadema) and Kubar Janggut Hitam (Taphozous melanopogon) are larger than males. This research contributes to understanding bat biodiversity in the Saung Cave area and highlights the ecological significance of these species in controlling insect populations.